Peningkatan Kapasitas Pelaku Fashion Melalui Pelatihan E-Commerce pada UMKM “Amanah Jaya” di Pasar Tambelang, Kabupaten Bekasi - M. Risky Yazid; Novi Fitria Hermiawati (Universitas 45 Surabaya, 2025)
Entrepreneurship is the process of identifying, developing and bringing a vision to life. This vision can be in the form of innovative ideas, sales ideas, opportunities, better ways of doing things. MSMEs have an important role in national economic growth, including the fast-growing fashion sector. However, the use of digital technology by MSMEs is still limited, especially in terms of marketing via e-commerce. This activity aims to increase the capacity of fashion players in the